Do letramento em saúde à competência em informação: espaço de interlocução - Gisele da Silva Rodrigues (2023)
This research had the main objective of investigating how studies in Health Literacy (LS) can contribute to the advancement of Information Literacy (CoInfo). The investigation was guided by eight categories, namely: terminology, conceptualization/definition, importance for health promotion, dimensional analysis, evaluation and measurement, emerging themes, institutional, and educational actions. Characterized as a bibliographic, exploratory, and qualitative research, this study sought to operationalize theoretical relationships to produce an analytical and critical synthesis. The theoretical-conceptual framework was synthesized from the contributions of foundational authors, comparing them with the collected data. Within the scope of the research, concepts involving studies about Literacy worldwide were addressed, including a historical-cultural synthesis of Information Literacy, the Ibero-American view, Media and Information Literacy, Critical Information Literacy, and the bias of informational literacy. Concepts related to Health Literacy, such as Digital Literacy, Digital Health Literacy, Artificial Intelligence Literacy, and Future Literacy were also addressed. Data collection was carried out through an Integrative Literature Review, in the time frame from 2012 to 2022, seeking articles that dealt with the interlocution between the themes. From this methodology, 10 articles were retrieved. The analysis and discussion of the data revealed significant study areas, such as collaboration between libraries and other health organizations, and the comprehensive view of the role of libraries and librarians in promoting health literacy. The critical review of concepts in other literacy domains indicated that CoInfo can contribute to the development of LS in various ways. In conclusion, this study demonstrated that studies in Health Literacy can indeed contribute to studies in Information Literacy. The research also highlighted the need for a research agenda focused on establishing clear and coherent relationships between the concepts, promoting a deeper and integrated understanding of these interrelated fields.